Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 4 - Section 4.9 - Antiderivatives - 4.9 Exercises: 59

Answer

$s(t) = -cos(t) - sin(t) + 1$

Work Step by Step

$v(t) = -1(-sin(t)) - cos(t)$ $s(t) = -cos(t) - sin(t) + C$ Given: $s(0) = 0$ $s(0) = -cos(0) - sin(0) + C$ $0 = -1 - 0 + C$ $0 = -1 + C$ $C = 1$ Replace $C$ in the original function with the newly found value: $s(t) = -cos(t) - sin(t) + 1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.